Consent of the damned : ordinary Argentinians in the dirty war - Sheinin, David (University Press of Florida, 2012)
An examination of the way the Argentinian military dictatorship was able to commit human rights abuses because it was abetted by the willingness of Argentine civilians to either ignore or either assist their perpetration.